EMPLOYING TALKING STICK TECHNIQUE TO DEVELOP SPEAKING ABILITY OF EFL LEARNERS - Lestari, Afriliani; Kamaruddin, Abd; Maf’ulah, Maf’ulah; Thamrin, Nur Sehang (Universitas Muhammadiyah Makassar, 2025)
This study set out to find out if grade 8 students at SMP Negeri 19 Palu could talk more fluently after using the Talking Stick Technique. This is a quantitative research study that evaluates the growth of students' speaking abilities using a quasi-experimental design with a pre-and post-test. The Talking Stick Technique significantly improved the students' speaking abilities, according to the results. The gathered data was statistically analyzed to identify any noteworthy variations between the experimental and control groups. According to the results, the experimental group's mean post-test score (60.26) was greater than that of the control group (47.70). Furthermore, the analysis of hypotheses showed that the T-test > Table (2.262 > 1.676). This demonstrates that the study's hypothesis was verified. In conclusion, eighth-grade students at SMP Negeri 19 Palu can improve their ability to speak by using the Talking Stick technique.